Comparison of two echocardiography-based methods for evaluating pediatric left ventricular diastolic dysfunction - Xiang, Xue; Zhu, Xu; Zheng, Min; Tang, Yi (Frontiers in Pediatrics, 2023)
Objectives To investigate the consistency between the 2016 America Society of Echocardiography (ASE)/European Association of Cardiovascular Imaging (EACVI) guideline-based recommendations and the body surface area (BSA)-transformed Z value-based cut-off for the assessment of left ventricular diastolic function (LVDF) in children. Methods Clinical data of children with heart failure (HF) and those with a high risk of HF and a low risk of HF were collected from the Children's Hospital of Chongqing Medical University between March 2021 and October 2022. The mitral annular e′ velocity, lateral E/e′ ratio, left atrial volume index, and peak tricuspid regurgitation velocity were detected by Echocardiography. The cut-off values recommended by the 2016 ASE/EACVI guidelines and the cut-off value based on the BSA-transformed Z value were used to evaluate LVDF. The consistencies and differences of the two criteria were compared. Results A total of 132 children with HF, 189 with a high risk of HF, and 231 with a low risk of HF, were enrolled. The consistency of the two criteria in evaluating LVDF in children with HF and with high risk of HF was moderate, with weighted kappa coefficients of 0.566 and 0.468, respectively (P < 0.001). The positivity rate of left ventricular diastolic dysfunction (LVDD) with Z value-based criteria (HF group, 23.5%; high-risk group, 8.5%) was higher than that with guideline-based criteria (HF group, 15.6%; high-risk group, 3.2%). In children with a low risk of HF, no case with LVDD was found. The consistency between the two criteria for grading the degree of LVDD was moderate, with a kappa coefficient of 0.522 (P = 0.001). The degree of LVDD according to the Z value-based criteria was higher than that of the guideline-based criteria (P = 0.004). Conclusions The Z value-based criteria used to evaluate LVDD in children with HF and high risk of HF may be more conducive to the early identification of LVDD, thereby permitting the possibility of early treatment intervention.